Novel T cell receptors reactive to the HPV16 E6 and E7 oncoproteins and strategy to potentiate their signaling strength using a co-stimulatory chimeric antigen receptor - Quirós Fernández, Isaac 1993- (2023)
More than 95% of all cervical cancer cases worldwide are caused by high-risk human papillomaviruses (HPV). The transformation and survival of the malignant HPV+ cells depend on the expression of the viral E6 and E7 oncoproteins, which makes them appropriate tumor-specific targets for immunotherapy. However, viral antigen presentation by tumor cells is generally low and limits the efficacy of tumor-reactive CD8+ T cells. In fact, adoptive cell therapies based on tumor-reactive T cell receptors (TCR) have shown limited efficacy as stand-alone treatments against solid tumors. In order to increase the efficacy of adoptive TCR-based immunotherapy of cancers caused by HPV16, a new strategy was devised combining an HPV16-specific TCR with a co-stimulatory chimeric antigen receptor (CAR). TCRs specific against the HPV16 E6 and E7 proteins were identified from the repertoire of healthy HLA-A2 donors and were characterized in terms of activation and cytotoxic capacity using the TCR-deficient Jurkat J76 cell line, and a novel NK-92-derived cell line capable of inducing TCR-mediated cytotoxicity. An E6-reactive TCR induced potent cytotoxicity towards HPV16+ cancer cell lines, while a TCR, reactive against the E7 protein showed weaker cytotoxicity against the HPV16+ cell lines tested. To enhance the specificity and signaling strength of the NK-92/TCR cells, a co-stimulatory CAR directed against the trophoblast cell surface antigen 2 (TROP2) was designed, carrying exclusively the intracellular domain of the inducible T cell co-stimulator protein (ICOS). NK-92 cells with co-expression of the E7-reactive TCR and the co-stimulatory CAR showed enhanced cytotoxicity against the HPV16+ and TROP2+ cancer cell lines. Overall, the data shows that a co-stimulatory TROP2-CAR can synergize with a tumor-specific TCR in NK-92 cells, enhancing their signaling strength and antigen-specific cytotoxicity. Such combination approach can help improve the efficacy of TCR-based adoptive...